Influence The Effectiveness of Compounds Produced From Algae Oscllatoria Princeps Agains t Bacteria and Detected of Some Fatty Acids - Al.Rubaiee, Ghaidaa; Shaukat, dauu (Iraqi Journal of Science, 2024)
In this study Oscillatoria princeps were isolated ،purified and identificationfrom water canal in Almustansiriah University . BG-11 culture media was used fortheir cultivation in suitable laboratory conditions (25c°, 200μE/mP2P/sec) for 16:8 hrs.Light: dark. Each culture was harvested at the end of exponential phase .Organicsolvents used for extraction was Chloroform: methanol at 2:1 to extract the crudeactive Intracellular and Extracellular substances, and evaporated down to dryness.Antibacterial activity of these different extracts were evaluated against 10 strains ofgram positive bacteria and gram negative bacteria, Agar diffusion method was usedin this evaluation. Results showed that the intracellular products which extractedbeast than extracellular product. The gram positive bacteria studied revealed highersusceptibility to attack by the intracellular and extracellular extracts comparing withthe gram negative bacteria. The intercellular extraction revealed higher antibacterialactivity against Staphylococcus arueus average of inhibition zone was 30mm. butThe extracellular extraction revealed higher antibacterial activity against Bacillussubtilise average of inhibition zone was 28 mm. However, Results showed gramnegative bacteria intracellular products extract has the antagonistic activity againstPseudomonas aeruginosas with 25 mm inhibition zone. also been detected on somefatty acids produced by the algae O.princeps which Palmitic , Stearic, Arachidic ,Linoleic and Linolenic . the highest rate is fatty acid Palmitic 75% of the extractintercellular while the rate of 34% of the acid fatty Linolenic to extracellularabroad.